- 2 - x = - 6
2 + x = 6
x = 4
2007-09-09 22:46:24
·
answer #1
·
answered by Como 7
·
0⤊
0⤋
x=4
2007-09-06 12:53:21
·
answer #2
·
answered by Steph 2
·
0⤊
0⤋
The golden rule to equations is "what you do to one side, you must do to the other side.
The goal is to isolate the varible
-2 - x = -6
add 2 to both sides
-2 - x = -6
+2 +2
solve that and you get
-x = -4
however, you can not have x as a negative, so multiply both sides by -1
-x = -4
-1 -1
-x * -1 = x
and -4 * -1 = 4
so you end up with
x = 4
2007-09-06 12:57:48
·
answer #3
·
answered by Zach 4
·
0⤊
0⤋
Okay, for this, you want all of your like terms to be on the same side. So I would move your -x to the other side by subtracting it, which will make it become a positive x which is necessary to solve this:
-2 = x - 6
From here, you'll add 6 to both sides to isolate your x
4 = x
And if you'd like to rewrite that as x = 4, you can. And that's your answer.
2007-09-06 12:53:28
·
answer #4
·
answered by aint_the_dakota 1
·
0⤊
0⤋
-2-x=-6
+x +x
-2=-6+x
+6 +6
4 =x
2007-09-06 12:51:46
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
-2-x=-6
-2+2-x=-6+2
-x=-4
x=4( divide both sides by -1 to get the answer)
2007-09-06 12:52:25
·
answer #6
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
-2-x=-6
+2=+2
-x=-4
-1=-1<===divide
x=4
2007-09-06 13:21:48
·
answer #7
·
answered by wendy f 3
·
0⤊
0⤋
-2 - x = -6
Add two to both sides
-x = -4
Negate both sides
x = 4
Done.
2007-09-06 12:51:57
·
answer #8
·
answered by PMP 5
·
0⤊
0⤋